Editorial - Teye, Prof. G. A. (UDS International Journal of Development, 2023)
The UDS International Journal of Development (UDSIJD) has published its second Issue for the year, Volume 10 No. 2, 2023. This Issue has a total of ten papers, four in Agricultural Sciences and six in the Humanities. All Directorates, Faculties and Schools of the University are encouraged to publish their research output with us. The Journal is open access and thus offers a wider coverage for their research output. We continue to encourage researchers, academics, and authors from varied fields to submit their research manuscripts for consideration and publication. The Editorial Team continues to be grateful to the University Management, authors, reviewers and staff of the Journal and all those who in diverse ways have supported in making this Issue of the Journal a reality. The Editor-in-Chief Prof. G. A. Teye